Virtue signaling and other heresies : selected writings from Whatever 2013-2018 - Scalzi, John, 1969- (Subterranean Press, 2018)
"For twenty years now--yes, twenty--John Scalzi has been writing on his blog Whatever, writing about, well, whatever: Politics, writing, cats, the internet and the great social and cultural events of our times. In that time he's gone from being just another crank online to being a bestselling, award-winning crank, i.e., the very best kind of crank there is. With Virtue Signaling and Other Heresies, Scalzi looks back on the years 2013 through 2018. In this volume, Scalzi delves through the final term of Obama and the ushering in of the Trump years, surveys the increasingly-hostil online landscape, goes to the movies, and talks on subjects ranging from #MeToo to the teachers who shaped him growing up. Through it all, Scalzi's distinct voice -- funny, sarcastic, passionate, sometimes angry, and honed by two decades of daily writing served up to hundreds of thousands of readers monthly--is on full display"--Jacket.